Education and innovation: An interview with Charles Chen Yidan - CHEN, Charles Yidan (Institutional Knowledge at Singapore Management University, 2019)
Education and innovation are not only the engines of economic growth in an increasingly knowledge-based global economy, but they also lead us to the solutions of the crises we face today.